ASSESSMENT OF ARTIFICIAL ENVIRONMENT FOR REPRODUCTION OF FOREST GREEN TREEFROG ALONG NIKKO-UTSUNOMIYA ROAD USING HABITAT EVALUATION PROCEDURE - H. Ito; A. Fukuda (Lowland Technology International, 2007)
This paper aimed to develop the SI (Suitability Index) models of Forest Green Treefrog and assess the reproduction and the environment created artificially along Nikko-Utsunomiya road using the models developed. The mitigation project was planned and carried out to create 4 artificial ponds for reproduction by the former Japan Highway Public Corporation near the roadside to protect Forest Green Treefrog since its reproduction environment was destructed by the road project. However, the mitigation project could not be evaluated quantitatively whether it was appropriate or not, because there was no environmental assessment method in Japan. Recently, in order to solve this problem, several organizations like the Ministry of Environment are trying to introduce the Habitat Evaluation Procedures (HEP). It can be applied to assess the quality and the value of the habitat for the target species by developing its SI models. Therefore, in this study, the SI models of Forest Green Treefrog were developed based on available information by reviewing existing studies, literatures, and interviewing the experts. Using developed SI models, the validity of HEP by utilizing the mitigation project along Nikko-Utsunomiya road was validated. Based on the results of the study, the applicability of HEP proved to be satisfactory.